Design and Build a Promotional and Online Ticket Ordering System for Guamanik Tourism - Febriantika Dwi Meridatama; Sharyanto Sharyanto; Bernadus Gunawan Sudarsono (Journal of Mathematics and Technology (MATECH), 2022)
Pecatu Beach or Guamanik Beach, also known as Guamanik Pecatu Park, is a beach located in Banyumanis Village, to the south of the Portuguese Fort Jepara, Central Java. Currently services in ticket purchase transactions are still done manually and transaction reports have not been stored properly because of the absence of a supporting system. From the description of the problems that occur, it is designed and built an Online Ticket Promotion and Booking Information System at Guamanik Tourism Web-Based which is expected to solve the existing problems. For the method of analysis and design used Unfield Modeling Language (UML). The Web-Based Information System for Promotion and Booking of Tickets at Guamanik Tourism uses the PHP and MySQL programming languages ​​as the database. The method used in completing this final project is the interview method, observation method and literature study method, design and testing. Which aims to provide information services to customers who need this information.